CORRELATION BETWEEN APOB100/APOA1 RATIO AND INSULIN RESISTANCE IN TYPE 2 DIABETES MELLITUS: Apolipoproteins and Type 2 diabetes mellitus - KUMARI N, SUCHETHA; SHETTY, SHILPA S (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Various lipid abnormalities are associated with Type 2 diabetes, thereby increasing the risk of cardiovascular disease and metabolic syndrome. The objective of the study is to correlate apolipoprotein ratio with insulin resistance (IR) to understand its role in Type 2 diabetes mellitus. Methods: The study population included 416 subjects of which 197 were non-diabetic and remaining 219 were non-diabetic and served as control subjects. Body mass index was calculated. Fasting plasma glucose, insulin, glycated hemoglobin levels, total cholesterol, triglyceride and high-density lipoprotein, ApoA-1, and ApoB-100 were measured using commercially available kits. Statistical analysis was performed with SPSS for Windows 16.0. Significance was defined as p<0.05. Results: Apolipoprotein A-1 levels were lower in the diabetic group whereas apolipoprotein B-100 levels, apolipoprotein ratios were higher in the diabetic group. ApoB100 and apolipoportein ratio showed a positive correlation with IR. Conclusions: The study results indicate that apolipoprotein B100/ApoA-1 ratio can act as a strong biomarker for IR.